Peningkatan Manajemen Keuangan SPPG Dalam Pengelolaan Anggaran Dan Biaya Operasional Program Makan Bergizi Gratis - Sani Haryati; Akhmad Hidayat Nurul Akbar (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This community service program aims to enhance the financial management capacity of the Nutrition Management Service Unit (SPPG) Tanjungkerta Suryalaya in managing budgets and operational costs of the Free Nutritious Meal Program. The partner faced several challenges, including the absence of systematic budgeting, inconsistent financial recordkeeping, and limited understanding of financial transparency and accountability. The program was implemented using a participatory approach consisting of socialization, financial management training, hands-on practice in budget preparation and simple financial recording, and evaluation. The training was conducted through face-to-face sessions involving core administrators, treasurers, and operational staff of SPPG. The results indicate a significant improvement in participants’ understanding and skills in preparing activity-based budgets, recording daily financial transactions, and separating program finances from personal finances. In addition, the program produced supporting documents such as draft budgets, simple cash book formats, and basic financial report templates that can be sustainably applied. It can be concluded that this community service activity strengthens financial transparency and accountability and supports the sustainability of the Free Nutritious Meal Program as part of efforts to improve community nutrition services.